1977
DOI: 10.1002/chin.197715198
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: 1,3‐ANIONIC CYCLOADDITIONS. XIII. ENDO‐EXO‐ISOMERIC CYCLOADDUCTS OF TRANS,TRANS‐1,3‐DIPHENYL‐2‐AZAALYLLITHIUM AND ACENAPHTHYLENE

Abstract: Das durch Umsetzung von N‐Benzyliden‐benzylamin mit Li‐diisopropylamid bei ‐60°C sowie durch thermische Ringöffnung von N‐Lithio‐cis‐ oder ‐trans‐2,3‐diphenylaziridin bei +65°C in THF‐Lösung darstellbare Azaallyl‐Li (I) cycloaddiert sich bei 0°C oder ‐70°C unter Retention an Acenaphthylen (II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The observed diastereoselectivities were not as high, however, in the formation of 6,5-bicyclic ring systems ( 45e , 45f ). To rationalize the observed stereochemical outcome, the authors proposed a model in which the 2-azaallyl anions adopt a W-shaped conformation (Scheme , inset), in accord with Kauffmann’s earlier studies. ,, …”
Section: -Azaallyl Anionsmentioning
confidence: 98%
See 2 more Smart Citations
“…The observed diastereoselectivities were not as high, however, in the formation of 6,5-bicyclic ring systems ( 45e , 45f ). To rationalize the observed stereochemical outcome, the authors proposed a model in which the 2-azaallyl anions adopt a W-shaped conformation (Scheme , inset), in accord with Kauffmann’s earlier studies. ,, …”
Section: -Azaallyl Anionsmentioning
confidence: 98%
“…As shown in Scheme 8, they found that the 1,3-diphenyl-2-azaallyl anion 6a, which was accessed via deprotonative ring-opening of aziridine 4, reacted with trans-stilbene (20), cis-stilbene (22), and acenaphthylene (25). 50,62 The relative configurations of the cycloadducts obtained from these reactions provided important mechanistic insights. 63 First, according to Woodward−Hoffmann rules, the ring-opening of cis-2,3-diphenylaziridine 4 should occur in a conrotatory fashion to afford Eimine isomer 6a′ as the product.…”
Section: Reactions Of Semistabilized 2-azaallyl Anions Generated Via ...mentioning
confidence: 99%
See 1 more Smart Citation